A pH-universal ORR catalyst with single-atom iron sites derived from a double-layer MOF for superior flexible quasi-solid-state rechargeable Zn–air batteries. Issue 12 (2nd November 2021) - Zhao, Meiqi; Liu, Haoran; Zhang, Hongwei; Chen, Wen; Sun, Hanqin; Wang, Zhenhua; Zhang, Biao; Song, Lin; Yang, Yong; Ma, Chao; Han, Yunhu; Huang, Wei
Abstract : The pH-universal ORR performance and reaction-mechanism scheme of the Fe1 /d-CN catalyst, which acts as the cathode for flexible quasi-solid-state alkaline/neutral rechargeable Zn–air batteries. Abstract : Developing a highly efficient, easy-to-fabricate and non-noble metal electrocatalyst is vital for the oxygen reduction reaction (ORR). Herein, we fabricate a single Fe site catalyst Fe1 /d-CN by developing a double-layer MOF strategy. The Fe1 /d-CN catalyst shows an excellent ORR activity in the pH-universal range, especially in alkaline electrolytes with a record-level half-wave potential of 0.950 V, exceeding those of almost all the reported non-noble electrocatalysts and the commercial Pt/C catalyst (0.863 V). Besides its exceptional ORR activity in alkaline electrolytes, it also exhibits comparable ORR activity to the commercial Pt/C catalyst in acidic and neutral electrolytes. We speculate that the sources of the excellent pH-universal ORR performance can be attributed to the regulation of the electronic structure of Fe centres and the excellent electron/proton transport capability that comes from the rich defects and hierarchical porous features of the Fe1 /d-CN catalyst. More excitingly, the catalyst possesses remarkable durability, and exhibits a negligible decrease after 30k accelerated durability test (ADT) cycles in pH-universal media. The flexible quasi-solid-state alkaline rechargeable Zn–air batteries with the Fe1 /d-CN catalyst as the cathode show superior performance such as a high OCV of 1.50 V and peak power density of 78.0 mW cm −2 . Furthermore, the flexible quasi-solid-state neutral rechargeable Zn–air batteries also exhibited remarkable performance.